Mouth Movements as Possible Cues of Social Interest at Birth: New Evidences for Early Communicative Behaviors - Guellai, Bahia; Streri, Arlette (Frontiers in Psychology, 2022)
Previous studies evidenced that different interactive contexts modulate newborns’ visual attention. In the present study, we investigated newborns’ motor feedback as an additional cue to neonates’ expression of interest. Using videos of interactive faces and a familiarization-test procedure, three different groups of newborns were assigned to three different conditions (i.e., one condition with a talking face during familiarization and silently moving faces at test, Silently moving/Silently condition, or Talking/Static condition). Following studies on neonatal imitation, mouth movements were analyzed as indicators of social interest. We expected newborns' occurrences of mouth movements to differ according to the different conditions: (a) whether or not the face in front of them was talking; and (b) if the person had been already seen or was new. Results revealed that a talking face elicited more motor feedback from the newborns than a silent one, and that there was no difference in front of the familiar face or the novel one. Finally, frequencies of mouth movements were greater, and latencies of appearance of the first mouth movement were shorter, in front of a static versus a dynamic face. These results are congruent with the idea of the existence of ‘a sense’ for interaction at birth, therefore new approaches in newborns’ studies are discussed.